Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Pendekatan Berbasis Kontekstual (CBA) terhadap Literasi Kimia Peserta Didik Kelas XI MIPA SMA Negeri Jakarta pada Materi Hidrolisis Garam - Ade Mutia; Tritiyatma Hadinugrahaningsih; Setia Budi (Jurnal Riset Pendidikan Kimia (JRPK), 2020)
This study aims to determine the positive effects of a guided inquiry learning model with a contextual based approach (CBA) on the chemical literacy of students of class XI MIPA SMA Negeri Jakarta in the hydrolysis of salt. This research was conducted in the even semester of the 2018/2019. This study uses quasi-experimental with post-test only non-equivalents design. The research sample amounted to 64 students of class XI MIPA C (control) and XI MIPA D (experiments) selected by purposive sampling technique. The posttest used to measure students' level of chemical literacy about salt hydrolysis. The results of this study indicate that the chemical literacy skills of experimental class students were 60.84% with a moderate category while the chemical literacy ability of the control group was 50.82% with a low category. After Independent Sample T-test (α = 0.05) t-stat value (2.597)> t-critical one tail value (1.669). It can be concluded that there is a positive effect of the guided inquiry learning model with a contextual based approach (CBA) on the chemical literacy of students of class XI MIPA SMA Negeri Jakarta in salt hydrolysis. Keywords: Guided Inquiry, Contextual Based Approach (CBA), Chemical Literacy, Salt Hydrolisis.